New species and new record of hadzioids (Amphipoda: Senticaudata, Hadzioidea) from the Persian Gulf, Iran - Momtazi, Farzaneh; Sari, Alireza; Maghsoudlou, Abdolvahab (Zootaxa, 2014)
New record and new species of the families Melitidae Bousfield, 1973 and Maeridae Krapp-Schickel, 2008 are described from the Iranian shorelines of the Persian Gulf. Melita persia sp. nov. is differentiated from other members of M. zeylanica Stebbing, 1904 group by: the presence of two setae on inner ramus of third uropod, the setal arrangement on the telson, and a recurved proximal lobe of sixth coxa in females. Also, Elasmopus menurte Barnard, 1974 previously described from Western Australia and Mauritius is recorded, for the first time, from Persian Gulf in the north-western Indian Ocean.